Temperament and emotional overeating: the mediating role of caregiver response to children’s negative emotions - Ju, Sehyun; Iwinski, Samantha; Bost, Kelly K. (Frontiers in Psychology, 2024)
Objective This study aimed to investigate the mediating effects of caregiver responses to a child’s negative emotions on the associations between infant temperament and emotional overeating in preschool children. Method A sample of 358 children and their caregivers enrolled in the STRONG Kids 2 (SK2) birth cohort study (N = 468) provided data for this analysis. Caregivers completed questionnaires assessing child temperament at 3 months, caregiver response to negative emotions at 18 months, and child emotional overeating at 36 months. Structural Equation Modeling was conducted using the lavaan package in RStudio to test hypothesized models examining whether the relations between early temperament and subsequent emotional eating were mediated by caregiver responses to a child’s emotions. Results Findings revealed that infant temperamental orienting/regulation predicted the later development of emotional overeating through supportive caregiver responses to a child’s negative emotions. Lower levels of orienting/regulation were associated with greater emotional overeating, explained by less supportive caregiver responses to the child’s emotions. Moreover, infant surgency had a positive direct influence on emotional overeating at 36 months. Both supportive and non-supportive caregiver responses to a child’s negative emotions had significant direct influences on emotional overeating. Conclusion The results highlight the importance of caregiver response to a child’s negative emotions as a mediator between infant temperament and emotional overeating in preschool children. Intervention strategies can be implemented to support caregivers in adopting supportive responses to their child’s negative emotions to promote healthy eating behaviors from early childhood. Future studies are needed to explore these pathways of influences throughout child development.